THE USE OF MOTHER TONGUE IN TEACHING MATHEMATICS - Edwin Lloyd T. Siyang, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Mathematical skills are often hard to acquire and master in a language unfamiliar to the learners. Oftentimes, students fail to master mathematical concepts and skills when they can hardly comprehend the medium of Instruction thus, this study explored the use of Mother Tongue in teaching Mathematics to selected Grade 9 students. The purpose was to examine the effectiveness of mother tongue-based instruction in teaching Mathematics. The study involved 60 grade 9 students of Bagong Barrio National High School. The research employed the experimental method which involved two groups, the experimental group and the control group, which were both given a pre-test and a post-test. The instrument used in the study is a written 30-item test which contains lessons about variations. Based on the findings, it is concluded that the use of mother tongue as a medium of instruction is more effective than the English language. Moreover, students who were taught using their native language showed a higher learning gain compared to those who were taught using English.